An IoT Framework for Real-Time Event Detection and Acquisition Using Mobile Sink - Prasad Nayak, Samaleswari; Champati Rai, Satyananda; Kumar Pradhan, Sateesh (International Journal of Engineering and Technology, 2018)
Immediate service provisioning with real-time attention to a critical patient at remote locations is a challenging task for health care unit personnel. Several incidents remain unattended for long duration due to tracking difficulties to the exact place of event. During accidents, natural calamities, any kind of disaster, providing the basic services to the affected people is a great challenge to the persons present nearby the location. This requires a real-time event status report collection, monitoring condition, arrange and provision system in place. Similarly during critical situation of a patient in hospital if the user requires blood platelet and plasma from a different centre to current place, which may not possible due to heavy traffic in the locality. In this regard we propose a quadcopter based mobile sink to navigate to the place, track, monitor and inform to the remote server which can also be treated as an intra-city delivery model. A gamepad is used to control the quadcopter from the nearby place, its movement mechanism is controlled by the integration of different sensors and other components. Several applications have been used in our model to control the position of quadcopter, capture images through sensors and forward the information to the destination to achieve the objective of real time data acquisition and assistance at the unreachable place of the event, with minimal delay.Â